EDUKASI CARA MENYIKAT GIGI BAGI SISWA SEKOLAH DASAR DENGAN MENGGUNAKAN APLIKASI TOUCH YOPICK - Octaviana, Devy; Heriyanto, Yonan; Cahyadi, Gugum; Laela, Dewi Sodja; Setyawan, Adhita Arif (Media Penelitian dan Pengembangan Kesehatan, 2023)
Information and Communication Technology is an important element in national and state life. Information technology has become the main facility for activities in various sectors of life, which has contributed greatly to fundamental changes in the operational structure and management of education, health and research. An application is a program that is ready to be used which is created to carry out a function for the user in solving problems using of this research is to dig up information on using the Touch YoPick Application, to find out how to brush your teeth using the Touch YoPick Application, to find out how to use the Touch YoPick Application properly. The design used in this research is a sequential exploratory mixed methods design. The first stage with qualitative research was to explore user needs for the YoPick Touch Application. The second stage is the application development stage so that a viable application is produced that meets user needs. Sampling used purposive sampling. The sample size was determined using the Slovin formula as 52 people. The results of the Touch YoPick Application make it easier for elementary school students to receive education about how to brush their teeth. It is hoped that the Touch YoPick application can also be used by other elementary schools. Measuring the level of technology readiness can be done using applications that function to develop the role of technology in the current digital era so that students can easily receive information.